Odpowiedzi

2010-02-18T20:17:44+01:00
A) 2(3x+4)-3(5x-6)+4(7x+8)=115
6x+8-15x+18+28x+32=115
6x-15x+28x=115-8-18-32
19x=57 | /19
x=3

b) x(x-5)-x(x+4)=-63
x²-5x-x²-4x=-63
x²-x²-5x-4x=-63
-9x=-63 | / (-9)
x=7

c) 6x-7(11+2x)+2=-4(15-x)+3x
6x-77-14x+2=-60+4x+3x
6x-14x-4x-3x=-60+77-2
-15x=15 | /(-15)
x=(-1)

d) 3(5x+3)=7(x+5)-3(2-x)
15x+9=7x+35-6+3x
15x-7x-3x=35-6-9
5x=20 | /5
x=4
  • Użytkownik Zadane
2010-02-18T20:17:56+01:00
A). 2(3x+4)-3(5x-6)+4(7x+8)=115
6x+8-15x+18+28x+32=115
6x-15x+28x=115-32-18-8
19x=57 /:19
x=3

b).x(x-5)-x(x+4)=-63
x²-5x-x²-4x=-63
-9x=-63 /:(-9)
x=7

c).6x-7(11+2x)+2=-4(15-x)+3x
6x-77-14x+2=-60+4x+3x
6x-14x-4x-3x=-60-2+77
-15x=15 /:(-15)
x=(-1)

d).3(5x+3)=7(x+5)-3(2-x)
15x+9=7x+35-6+3x
15x-7x-3x=35-6-9
5x=20 /:5
x=4
2010-02-18T20:31:50+01:00
A). 2(3x+4)-3(5x-6)+4(7x+8)=115
6x+8-15x+18+28x+32=115
19x+58=115
19x=57
x=3

b).x(x-5)-x(x+4)=-63
x(kwadrat)-5x-x(kwadrat)-4x=-63
-9x=-63
x=7

c).6x-7(11+2x)+2=-4(15-x)+3x
6x-77-14x+2=-60+4x+3x
-8x-75=-60+7x
-x=-15
x=15


d).3(5x+3)=7(x+5)-3(2-x)
15x+9=7x+35-6+3x
15x+9=10x+29
5x=20
x=4